Work of Art and Nature in the Transcendental of Freudian Metapsychology in Paul Ricoeur - Bertorello, Adrián (2016)
The purpose of this article is to investigate the aporia of the epistemological status of Freudian metapsychology as represented by Ricoeur’s hermeneutics. This aporia centers on the concept of psychic nature as the ultimate target of metapsychological speculation. The question this article addresses is whether the psychic apparatus that emerges from metapsychological speculation responds to a conception of nature that belongs to a physical model or a phenomenological model. This question has an ambiguous answer in Ricoeur’s work. In order to show the ambiguity, we begin by examining the transcendental reading Ricoeur makes of metapsychology. Then, we explain the aporia of Freudian naturalism, and following a suggestion by Ricoeur, we indicate a way out of it through the argumentative reconstruction of the relationship between artwork and psychic nature.